PENGARUH PRAKTIK PENJUALAN TERHADAP MINAT BERWIRAUSAHA SISWA PROGRAM KEAHLIAN BISNIS DAN PEMASARAN SMK NEGERI 1 KOTA BENGKULU - Helmarini Helmarini (Jurnal AkunStie (JAS), 2019)
This study aims to determine the effect of sales practices on students' entrepreneurial interest in the Business and Marketing Expertise Program at vocational high school 1 city of Bengkulu.This type of research is a quantitative approach descriptive research. The population in this study were students of class X Business and Marketing Skills Program at vocational high school 1 city of Bengkulu who had conducted sales practices totaling 66 students. The sample used is the total sample (total sampling). Data collection techniques using observation, questionnaires, interviews, and documentation. Data analysis techniques use: Simple Linear Regression. The results of this study indicate that: (1) sales practices by students obtained an average value of 63, which is in the interval (63-75) in the excellent category. (2) the interest of entrepreneurship in Business and Marketing Expertise Program at vocational high school 1 city of Bengkulu obtained an average value of 64.15 which is in the interval (63-75) in the excellent category. (3) there is a significant influence of sales practices on students' interest in entrepreneurship in Business and Marketing Skills Program at vocational high school 1 city of Bengkulu. The results of a simple linear regression test seen from sales practices on student entrepreneurial interest shows that the calculated F value = 32.881 is greater than Ftable = 3.99. Thus Ha was accepted while Ho was rejected, the magnitude of the effect of sales practices on student entrepreneurial interest was 34.32%.